Legal Protection and Certainty of Taxpayers’ Rights and Obligations in the Perspective of Government Regulation Number. 50 of 2022 - Shashia Andini Kristianto; Gunardi Lie (Universitas Ibn Khaldun Bogor, 2026)
This article examines legal protection and the certainty of taxpayers’ rights and obligations from the perspective of Government Regulation Number 50 of 2022, as well as the position of the Taxpayer Charter in strengthening legal protection and encouraging tax compliance in Indonesia. This study employs a normative legal research method using a statutory approach and a conceptual approach. The results of the discussion show that Government Regulation Number 50 of 2022 provides a clearer foundation regarding the procedures for the implementation of taxpayers’ rights and the fulfillment of their obligations, thereby functioning as an important instrument in realizing legal certainty, justice, and a balanced legal relationship between the state and taxpayers. These regulations cover the rights to information, services, data protection, restitution, objection, appeal, and complaint, as well as administrative obligations such as taxpayer identification number registration, tax return submission, tax payment, bookkeeping, and a cooperative attitude during tax audits. In addition, the Taxpayer Charter is understood as a complementary instrument that codifies taxpayers’ rights and obligations in a simpler and more understandable manner, thereby supporting the creation of better services, more concrete legal protection, and voluntary compliance within the self-assessment system. Thus, the clarity of the regulation of rights, obligations, law enforcement mechanisms, and tax dispute resolution becomes an important factor in building a tax system that is fair, transparent, credible, and based on legal certainty.